External validation of the REMEMBER score - Peivandi, Armin Darius; Welp, Henryk; Kintrup, Sebastian; Wagner, Nana Maria; Dell’Aquila, Angelo Maria (Frontiers in Cardiovascular Medicine, 2023)
Background The use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) after coronary artery bypass grafting (CABG) is associated with high in-hospital mortality rates. The pRedicting mortality in patients undergoing venoarterial Extracorporeal MEMBrane oxygenation after coronary artEry bypass gRafting (REMEMBER) score has been created to predict in-hospital mortality in this subgroup of patients. The aim of this study is to externally validate the REMEMBER score. Methods All CABG patients who received VA-ECMO during or after the operation at our center between 01/2012 and 12/2021 were included in the analysis. Discrimination was assessed using concordance statistics, visualized by ROC curve analysis. Calibration-in-the-large and Calibration slope were tested separately. Results A total of 107 patients (male: n = 78, 72.9%) were included in this study. The in-hospital mortality rate in our cohort was 45.8% compared with 55% in the original study. The REMEMBER score median predicted mortality rate was 52% (76.9–36%). However, the REMEMBER score showed low discriminative ability [AUC: 0.623 (p = 0.0244; 95% CI = 0.524–0.715)] and inaccurate calibration (intercept = 0.25074; p = 0.0195; slope = 0.39504; p = 0.0303), indicating poor performance. Conclusions The REMEMBER score did not predict in-hospital mortality and was therefore not applicable in our cohort of patients. Additional external validation studies in a multicenter setting are therefore advisable.